2020
DOI: 10.3389/fnbeh.2020.00012
|View full text |Cite
|
Sign up to set email alerts
|

Differential Phosphorylation of the Glucocorticoid Receptor in Hippocampal Subregions Induced by Contextual Fear Conditioning Training

Abstract: Aversive events induce the release of glucocorticoid stress hormones that facilitate long-term memory consolidation, an effect that depends on the activation of glucocorticoid receptors (GRs). GRs are distributed widely in the hippocampus. The dorsal region of the hippocampus has been related to cognitive functions and the ventral region to stress and emotion. GR acts as a transcription factor which after hormone binding becomes phosphorylated, affecting its cellular distribution and transcriptional activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…Recently, it was reported that plasmatic glucocorticoids levels increase after a CFC task and also does the Ser246 phosphorylation of GR in the dorsal hippocampus, which is associated with binding to co‐repressors inside the nucleus and transcription‐silencing (Ponce‐Lina et al., 2020). Although this fact is opposed to the stress‐induced gene transcription, this work proposes that an increase in pSer246 could inhibit the expression of genes that are not required for memory acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that plasmatic glucocorticoids levels increase after a CFC task and also does the Ser246 phosphorylation of GR in the dorsal hippocampus, which is associated with binding to co‐repressors inside the nucleus and transcription‐silencing (Ponce‐Lina et al., 2020). Although this fact is opposed to the stress‐induced gene transcription, this work proposes that an increase in pSer246 could inhibit the expression of genes that are not required for memory acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the dorsal hippocampus is vital for spatial learning, and is particularly critical in mediating contextual discrimination (Fanselow & Dong, 2010;Wells et al, 2011). However, the ventral hippocampus is strongly associated with negative affective symptoms (Felix-Ortiz et al, 2013;Jimenez et al, 2020;Kaouane et al, 2020;Kim et al, 2020;Pinizzotto et al, 2020;Ponce-Lina et al, 2020). Similar functional differences along the septo-temporal axis of the hippocampus have been noted in humans, with ventral hippocampus demonstrating greater activity in response to negative affective symptoms (Lau et al, 2010;Strange et al, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…SDS-PAGE and Western blot were performed as previously described ( Ponce-Lina et al, 2020 ). Membranes were incubated with a goat anti-rabbit secondary antibody conjugated to horseradish peroxidase (1:3,000; Invitrogen, United States, #ab6721) for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%